Integrating Islamic microfinance literacy in pesantren: a community-based approach to economic empowerment - Nisma (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Rural pesantren communities in East Java play a central role in socio-religious life, yet many santri and micro-entrepreneurs lack adequate literacy in Islamic microfinance, limiting access to halal financial services. Objective: This program aimed to strengthen Islamic microfinance literacy and facilitate institutional access for pesantren-based micro-entrepreneurs through a participatory, community-centered approach. Method: A backward-designed framework was applied, integrating needs assessment, contextualized training, simulation-based learning, sustained mentoring, and collaboration with local sharia financial institutions. Results: The program improved participants’ understanding of Islamic financial contracts, increased confidence in financial decision-making, and encouraged formal engagement with sharia microfinance services, alongside the strengthening of collective economic groups and institutional linkages within pesantren communities. Implication: These findings suggest that participatory and mentoring-based financial literacy programs can effectively enhance access to inclusive and faith-based financial systems in rural contexts. Novelty: The program introduces a pesantren-based model that combines experiential learning, sustained mentoring, and institutional collaboration as a scalable approach to Islamic microfinance empowerment beyond conventional short-term training.